The impact of spatial design to avoid gadget addiction among children (ARTEKS : Jurnal Teknik Arsitektur, 2023)
Technology plays an essential role in people's lives. These include smartphones, tablets, iPhones, television and others. In today's cultures, gadgets have become a trend for life and information, not just communication. All information and dailies, including shopping, payment and entertainment, are provided on this device. Users of gadgets are very heterogeneous, from older adults to the young child. Unfortunately, gadgets are also popular among children, bringing both positive and negative impacts for children. Excessive use of technology such as gadgets among children will cause a side effect for them. They spend large amounts of time doing these things while ignoring their body posture, screen brightness, and having a very near screen distance from their eyes, affecting their vision and health. Some parents use the gadget as an easy way to calm down their kids when they are in a tantrum. As a result, significant attention is required from socials and communities where children grow and develop, such as parents, caregivers, educators in early childhood education schools, and society as a whole, to reduce the adverse effects of gadgets on children.
Keywords: Children; Gadged; Interactive playground; Interior design